UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MENDESKRIPSIKAN RANGKIANG DISAMPING RUMAH GADANG DALAM MATA PELAJARAN BAM MELALUI MODEL PEMBELAJARAN KOOPERATIVE TIPE TIME TOKEN PADA SISWA KELAS VIII.1 SMPN 4 PASAMAN - Sulastri, Tita (STKIP Pesisir Selatan, 2018)
Based on the learning outcomes of Class VIII.1 Pasaman Junior High School 4 in the BAM sub subject, describing the rangkiang beside rumah gadang, it was found that the student learning outcomes in BAM subjects were still very low. The average student learning outcomes are still below the KKM. The purpose of this study was to describe and obtain information about efforts to improve student learning outcomes in BAM sub subjects. Describe the rangkiang next to the rumah gadang through the cooperative learning model of Time Token Type in Class VIII.1 Pasaman Middle School 4 West Pasaman Regency. This research is a classroom action research. The research procedure in this study includes planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 23 students of Class VIII.1 Pasaman 4 Middle School. Research data was collected using observation sheets and daily tests. Data is analyzed using percentages. Based on the results of the research and discussion that has been raised, it can be concluded that the cooperative learning model of Time Token Type can improve student learning outcomes in BAM sub subjects. Describe the addition of a traditional house in Pasaman 4 Middle School. Student learning outcomes from cycle I to cycle II. Student learning outcomes in cycle I was 52.84 (Enough) increased to 84.26 (Good) with an increase of 32.42%.